Implementasi Pembelajaran Akhlaku Lil Banat sebagai Upaya Mengurangi Kenakalan Remaja di Dusun 2 Desa Sumbersari - Arifin, Abdul Aziz; Gumilar, Restu Syawa; Silvia, Saskia Siti; Anditasari, Putri (Fisip UIN Sunan Gunung Djati Bandung, 2025)
Juvenile delinquency is one of the social problems that often occur in the community, including in Hamlet 2 Sumbersari Village. To overcome this problem, efforts are needed that focus on the formation of good character and morals from an early age. This study aims to evaluate the implementation of Lil Banat Akhlaku learning as one of the efforts to reduce juvenile delinquency in Hamlet 2, Sumbersari Village. The method used in this study is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the implementation of Lil Banat Akhlaku learning has had a positive impact on the behavior of adolescents in the hamlet. The youth involved in this program showed an improvement in attitudes of discipline, responsibility, and concern for others. Thus, Lil Banat Akhlaku learning can be used as an effective learning model in shaping a better character of adolescents and as a preventive effort in reducing juvenile delinquency in society.